Translation and validation of a patient satisfaction survey: The isiXhosa version - Tania Steyl; Julie Phillips (AOSIS, 2013)
Background: Although the use of surveys has been supported for assessing understanding of health care service quality, it could also be argued that their main function is to quantify perceptions. The importance of assessing patient satisfaction in individuals' own language has been highlighted in research. However, important culture-specific differences can be revealed during the adaptation process of a scale, and if not attended to can influence the validity ofthe scale. Objectives: The aim of this study was to assess the validity and reliability of the isiXhosa version of the Patient Survey for Quality of Care (PSQC) in primary health care (PHC) facilities in a selected district in the Western Cape, South Africa. Method: The PSQC was translated into isiXhosa by two independant translators and the translated back into English by a third translator. All three translators reviewed the back translation. Face and content validity of the scale were assessed. Fifteen isiXhosa-speaking clients with type 2 diabetes mellitus who had a mean age of 62.27 years (SD 10.33) and came from a randomly selected community health centre participated in the test-retest reliability. Results: Internal consistency of the scale was good (Cronbach alpha 0.70). Alpha values of individual items relating to quality of care as well as items flagged for inferior service quality were between 0.772 and 1.000, indicating good to high internal consistency. Conclusion: Results of this study indicated that the isiXhosa version of the PSQC was as reliable as the English version. It can be implemented at PHC level to assess isiXhosa-speaking patients' satisfaction with health care services.